"Sekunder förvandlas till år": Återfödelse, återklingande och återskapande i sjuttiotalsrock - Hyltén-Cavallius, Sverker (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
The aim of the article is to explore ways to conceiving and organizing the past in popular music. Empirical basis is observations at music events and internet discussions, and analysis of recorded music, conducted within a current research project. The article develops three retrologies, literally "ways of thinking back". Rebirth is when musicians disappear and after many years reappear. In this case identity — the authority to claim personal continuity — and the capability to represent and manage a lost context, are keys to an authentic performance and central to the musicians’ chances to update and develop their sound. Resounding is the use of past sounds, instruments, grooves and melodic fragments that are put together in new ways. These bands are associated to the 70’s, and listeners will find a number of historic references yet rarely or never find actual copies. Recreation is the meticulous work characterizing certain tribute bands in their effort to recreate historical concerts. In this case, the identity of the performing artist is erased in favor of the identity of the performed artist, placing authenticity in the matching of detailed performance and audience expectations. Any improvisations would here be regarded as mistakes. To conclude, each retrology points to different conceptions of authenticity, but all place high value in mastering contextual knowledge.